La RSE : nouvelle forme de dé-marchandisation du monde ? - Nicolas Postel; Richard Sobel (Développement Durable et Territoires)
The movement says about “CSR” tries to reconcile the current financial mode of accumulation with certain social and environmental requirements. This movement joins well enough in the historic and institutionnalist analysis which Karl Polanyi made of the limits of marchandisation of the world. Indeed, this movement consists in returning on excess strong marchandisation of the relationship with the nature and with the work which would have pulled the new capitalism. In reaction, this movement mobilizes the individual commitment to build a new “great transformation”, that is new articulation between social justice and efficacity to assure the viability of the capitalism. It means extending economic comportment in the other thing than the simple maximization of the short-term individual interests. This article aims at exploiting this nearness between the movement of the CSR and the analysis. The stake is to determine in which measure the CSR constitutes a relevant answer to the necessary collective management of the fiction which establishes the apparent marchandisation of money, labour and nature.